The association between mammography reports and women’s age using retrospective data form a medical system - Chang, Wen-Mi; Chen, Yi-Chun; Lu, I-Cheng; Chen, Jen-Lung; Chuang, Hung-Yi (Frontiers in Global Women's Health, 2025)
ObjectiveWe explored the association of age, obesity and marital status with Breast Imaging Reporting and Data System (BI-RADS) category distribution in women, using retrospective mammography data from a medical system, as only a few studies have investigated this association.Materials and methodsThis retrospective study collected the first left-lateral and right-lateral mammography data of 4,165 and 4,213 women from 2,011 to 2020 in a medical system, respectively, to be analyzed. We examined the association of age, body mass index (BMI), and marital status with BI-RADS categories using the Chi-square test and multinomial logistic regression.ResultsThe proportion of BI-RADS category 0 decreased with age, but the proportion of BI-RADS categories 4 and 5 increased with age. Women aged >69 years had a higher proportion of BI-RADS categories 4 and 5 [adjusted odds ratio (aOR) = 1.34 for left-lateral mammography and aOR = 1.29 for right-lateral mammography data] than women aged 45–69 years. Overweight was associated with the rate of the proportion of BI-RADS categories 4 and 5 of the left-lateral breast (aOR = 1.26, p < 0.05) but not with the right-lateral breast.ConclusionsAge >69 years, being overweight, and being separated/divorced/widowed were the factors associated with BI-RADS categories 4 and 5 of women who underwent mammography.